Computerized information retrieval: individual differences in the use of spatial vs nonspatial navigational information. - Westerman, S. J. (Perceptual & Motor Skills)
Although a number of experiments have demonstrated the importance of spatial ability as a predictor of computer-based performance, there is little evidence relating to the mechanics of this association or the implications for interface design. Two experiments on the relative importance of spatial and nonspatial semantic information within the context of computerized information retrieval are described. The first experiment indicated that spatial ability did not interact with the spatial information content of the computer interface. The second experiment indicated that the effects of spatial ability are attenuated when additional nonspatial semantic information is provided. Reprinted by permission of the publisher, 1995.